EXPLORING CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE: THE CASE OF ISLAMIC BANKS IN INDONESIA - Nur Fathonah, Andina; Ihsan Zulfikar Darmawan, Muhammad; Zulfi Rachmatullah, Muhammad; Alif Fauzani, Muhammad; Aulia Zahra, Mustika (International Journal of Psychosocial Rehabilitation, 2020)
Banking institutions are an alternative financial institution chosen by the people in this modern era. As the economy develops in Indonesia, sharia-based banking appears. Of course, every Islamic financial institution with its business uniqueness has the task of practicing Islamic business in all its activities. In accordance with UU RI No.25 Tahun 2007 about Penanaman Modal Pasal 15, investors are obliged to carry out company responsibilities. This is confirmed by UU RI No.40 Tahun 2007 about Perseroan Terbatas Pasal 74 (3), companies which do not carry out their obligations will be sanctioned with laws and regulations.The responsibility of the company in this case, is that Islamic financial institutions are committed to carrying out real tasks in the social and environmental dimensions. According to Rama and Meliawati (2014), the concept of CSR in Islam is more a form of humanity's devotion to Allah SWT in the corporate dimension. According to Othman and Azlan (2010), there are eight dimensions that are used as benchmarks for disclosure of CSR, namely finance and investment, products and services, employees, society, environment, and corporate governance.In carrying out its social responsibilities, CSR focuses its attention on three things, namely profit (profit), society (people), and the environment (planet). The company must have an adequate level of profitability because profits are the foundation for the company to be able to develop and maintain its existence (Darmawati, 2014). Profitability ratio is a ratio to show how much the company's ability to make a profit. The ratio used in this study is Return on Equity (ROE). Based on the data that the writer re-examined, the value of ICSR Bank Syariah Mandiri from 2015 to 2016 increased by 0.0417 but the value of Return On Equity (ROE) decreased by 0,0007. This phenomenon is what drives the author to examine the ICSR on ROE.